The territory of Poetovio and the boundary between Noricum and Pannonia - Ragolič, Anja (Arheološki vestnik, 2013)
The article contains a new attempt at delimiting the territory of the Roman city of Poetovio. It is a topic tackled in few studies by the past and the article begins with their brief presentation. In the absence of boundary stones or other clear markers, the boundary was sought through the use of Thiessen polygons and GIS analyses, which were then compared to the few existing literary sources, as well as archaeological and epigraphic finds. The results enabled a theoretical boundary of Poetovio’s territory to be proposed, with the most problematic part being its northern boundary.